2019
DOI: 10.1088/1755-1315/295/3/032083
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Motivation and Path of New Logistics Development under the New Retail Era

Abstract: New retail is a retail model based on the Internet, using big data, cloud computing and other technologies to upgrade the production process, circulation and sales of commodities, and deep integration of online and offline and smart logistics. The new retail has aroused widespread concern from all walks of life, and the new retail industry has sprung up, which has also promoted the development of new logistics. By analyzing the relationship between new retail and new logistics development, the article explores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effective integration of online and offline channels is the new foundation for the modern retail industry. Many traditional retailers are catching up with this trend in order to meet current customers' increasing complexities and needs [33][34][35]. Scholars [36] have found that, in cross-border e-commerce, eight factors (training, performance, user-friendliness, trust, usability, security, quality, and design) significantly affect e-service satisfaction.…”
Section: Online-merge-offline Service Featuresmentioning
confidence: 99%
“…The effective integration of online and offline channels is the new foundation for the modern retail industry. Many traditional retailers are catching up with this trend in order to meet current customers' increasing complexities and needs [33][34][35]. Scholars [36] have found that, in cross-border e-commerce, eight factors (training, performance, user-friendliness, trust, usability, security, quality, and design) significantly affect e-service satisfaction.…”
Section: Online-merge-offline Service Featuresmentioning
confidence: 99%
“…In the new era of technology‐enabled retail, the application of intelligent technology in circulation networks can improve the accuracy and efficiency of the logistics process timelier (Shen et al, 2019). Moreover, commodity circulation firms engage more closely with consumers and can better grasp consumers' demands in the process of ILT to achieve better performance (Wang et al, 2019). Therefore, compared with production manufacturing firms, commodity circulation firms have good information foundation and rich practical experience in ILT and thus enjoy more advantages in this area.…”
Section: Hypotheses and Conceptual Research Frameworkmentioning
confidence: 99%
“…Intelligent logistics. Intelligent logistics are planned, managed or controlled in a more intelligent way (Mcfarlane et al, 2016), by combining high-tech to rationally allocate resources and promote the transformation and development of modern supply chains with sharing and innovation (Wang et al, 2019). AI is already changing logistics and transportation in the retailing industry, and intelligent route planning, self-driving vehicles, robot deliveries and drones are some of its exciting new developments (Shankar, 2018).…”
Section: Introductionmentioning
confidence: 99%